Angiostrongylus vasorum infection in a fox - Brizzio, Renata; Degiovanni, Cecilia; Martin, Ana Maria (Brazilian Journal of Veterinary Pathology, 2025)
A juvenile, gray fox arrived at the zoo with dehydration, depression and poor body condition. He died the day after arrival.